The Efficacy of Fan Therapy to Alleviate Breathlessness among Lung Cancer Patients - Noviantari, Komang (Jurnal Kesehatan, 2024)
Breathlessness is a commonly reported symptom among patients with advanced-stage lung cancer and significantly affects their quality of life. Nowadays, treating breathlessness using standard pharmacological therapies is considered not very effective. Fan therapy, as one of the non-pharmacological approaches, emerges as a way to treat breathlessness. This study aims to examine fan therapy's impact on alleviating breathlessness in lung cancer patients. The research employs a literature review methodology, searching for relevant articles from 2017 to 2022 in databases such as Science Direct, EBSCOhost, Clinical Key Nursing, PubMed, and Google Scholar. Five eligible articles are analyzed descriptively. The findings reveal that 80% of the articles assert the effectiveness of fan therapy in reducing breathlessness in lung cancer patients. Meanwhile, 20% of the articles suggest that fan therapy may have clinical benefits in managing breathlessness. Additionally, it was found that fan therapy can decrease respiratory rates in 60% of the articles and enhance peripheral oxygen saturation in 20% of the articles. Notably, no adverse side effects on patients were reported across all analyzed articles. In conclusion, fan therapy emerges as an economical and safe non-pharmacological intervention for mitigating breathlessness in patients with advanced-stage lung cancer.